Manajmen Teknis Penerimaan Dana Hibah di Pemerintahan Daerah Kabupaten Subang Bagian Kesejateraan Masyarakat - Siti Robiah Adawiyah; Salma Tiara Aqila; Septian Eka Prahardik; Ahmad Farihin (STIT Fatahillah, 2023)
The articel is the result of field research on “the technical management of grants grants” at the subang district government office of the subang public welfare section (kesra). Aimed at figuring out how to process the application, aligntment, reception until the monitoring of the grant evaluation. The approach method used in this study is a case study method. The data sources used in the stydy include primary in secondary data sources. A qualitative approach is used to collect and analyze the data in the study. The method of applying data collection includes observation, interviews and documentation. Management is a skill in accomplishing tasks through the help of others. The grant is one of the sources of income and expenditures used to finance programs in the region.